Destination Loyalty Model of Elderly Foreign Tourists Visiting Bali - Rai Utama, I Gusti Bagus; Darma Putra, Nyoman; Suradnya, I Made (E-Journal of Tourism; Volume 1 Number 1 (March 2014), 2014)
Research was designed to understand loyalty model of elderly foreign tourists visiitng Bali which was undertaken in the main destinations in Bali i.e., Kuta, Nusa Dua, Sanur, Ubud and Lovina. 400 respondents were determined purposively. The criteria were senior tourists aged 55 or over and tourists vacationing in one of Bali’s tourism destinations. Descriptive statistical analysis and the SEM-AMOS structural model analysis tools were undertaken to analyze statistically. The resuts show that (1) Internal motivation does not have a significant effect on destination image. (2) External motivation has a significant effect on destination image and loyalty, but does not have a significant effect on tourist’s satisfaction. (3) Destination image has a significant effect on tourist’s satisfaction. (4) Tourist’s satisfaction has a significant effect on destination loyalty. Two loyalty models were formed: (1) Destination loyalty is directly influenced by tourist’s satisfaction, and indirectly influenced by destination image and external motivation. (2) Destination loyalty is directly influenced by external motivation, but the influence is not as significant as the influence of tourist’s satisfaction on loyalty. Suggestions of the research are maintaining the joint approach to answer various questions through quantitative approach. Improvement strong image of Bali is crucial, such as: (1) improving uniqueness of culture, (2) welcoming local inhabitants, (3) improving tourism infrastructure, and (4) comfortable tourism atmosphere.
Keywords: elderly foreign tourists, internal motivation, external motivation, destination image, tourist’s satisfaction, tourist’s loyalty